Using AquaCrop for Irrigation and water productivity assessment of Table grapes in arid region of Mexico - Er-Raki Salah; Bouras Elhoussaine; Rodriguez Julio Cesar; CruzBautista Fidencio; Watts Chriss; Lizarraga-Celaya Carlos; Chehbouni Abdelghani (E3S Web of Conferences, 2024)
The aim of this work is to use the AquaCrop model for irrigation and water productivity assessment of Table grapes in arid region of Mexico during 2005 and 2006 cropping seasons. The irrigation efficiency was investigated by comparing the irrigation scheduling design used by the farmer to the AquaCrop model recommendations. Data analysis showed that the farmer irrigates almost every day, which results in the water content in the root zone always exceeding the soil moisture at field capacity (FC). This generates substantial losses of water through deep percolation. By using the AquaCrop model, the optimization of irrigation water scheduling in order to avoid both water stress and deep percolation was about 547 mm and 510 mm, which it is about half of what was applied by the farmer (1006 mm and 930 mm) during 2005 and 2006, respectively. This large difference, lost through deep percolation, reduces the water productivity (WP) by about 45%.